2007
DOI: 10.1371/journal.pcbi.0030167
|View full text |Cite
|
Sign up to set email alerts
|

Functional Representation of Enzymes by Specific Peptides

Abstract: Predicting the function of a protein from its sequence is a long-standing goal of bioinformatic research. While sequence similarity is the most popular tool used for this purpose, sequence motifs may also subserve this goal. Here we develop a motif-based method consisting of applying an unsupervised motif extraction algorithm (MEX) to all enzyme sequences, and filtering the results by the four-level classification hierarchy of the Enzyme Commission (EC). The resulting motifs serve as specific peptides (SPs), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…As a result, cases of remote homology which may be captured by DME could have been missed by BLAST-based assignments, as was demonstrated by [6] and by [8]. The SP-based search has two other advantages over BLAST: it is conceptually simpler, relying only on a look-up table, and it points to specific locations on the queried protein which may be relevant to the expected catalytic function of that enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, cases of remote homology which may be captured by DME could have been missed by BLAST-based assignments, as was demonstrated by [6] and by [8]. The SP-based search has two other advantages over BLAST: it is conceptually simpler, relying only on a look-up table, and it points to specific locations on the queried protein which may be relevant to the expected catalytic function of that enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…The study by Kunik et al (2007) has answered this question affirmatively. It has applied MEX to a large set of proteins known as enzymes, derived from the Swiss-Prot database (release 48.3 in Oct 2005).…”
Section: Specific Peptidesmentioning
confidence: 91%
“…Such a comparison, based on linear SVM (Vapnik 1995;Scholkopf 1997) training and testing on the class of oxidoreductases leads to the conclusion that MEX motifs do better than the other methods (Kunik et al 2007).…”
Section: Specific Peptidesmentioning
confidence: 99%
“…Based on MEX, Kunik et al [38] have developed a method to identify and classify enzymes based on Specific Peptides (SPs). The SPs are strings of amino acids, derived from enzyme sequences using MEX and showed that the coverage of the SPs is better than that of PROSITE motifs in finding the function of enzyme families.…”
Section: Methods By Feature Spacementioning
confidence: 99%